Application of robotic technology in surgery (literature review) - D. G. Parfeev; A. M. Morozov; K. I. Khorak; P. G. Kogan; S. V. Zhukov; A. D. Aminova; V. A. Zhezheleva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. Modern medicine is closely intertwined with engineering and technology. Robotic surgery is one of the most promising and fastest growing fields in the world. The growth of the global surgical robots market is driven by several factors including aging population, rising income levels, increasing healthcare expenditure, benefits of robotic surgeries, rising incidence of chronic diseases and support from government authorities and advancements in diagnostic technologies. Robots enable complex surgical interventions with minimal invasiveness. At the same time, there are barriers to the development of robotic technology, such as the high cost of robots and procedures, as well as a shortage of qualified specialists. The purpose of study. Evaluate the possibilities of robotic technology application in surgery. Materials and methods. In the course of the present study, we searched and analyzed current literature data from domestic and foreign sources on the application of robotic technologies in surgery. Results. Since the introduction of robotic systems in surgery, such as da Vinci, medical practice has undergone significant changes. Robotic-assisted surgical interventions have been of particular interest and demand in recent times and are gradually being introduced into various fields of modern medicine. Robotic surgical technologies provide higher precision and minimally invasive procedures, which helps to reduce the patient's recovery time and decrease the rate of postoperative complications. One of the main advantages of robotic surgery is the ability to perform complex manipulations with a high degree of precision. Three-dimensional image magnification and stability of the instruments allow the surgeon to better see and control the process, which, in turn, minimizes the risk of damage to healthy tissues and organs. Conclusion. Robotization is currently becoming increasingly widespread in various branches of medicine, including surgery. Modern robotic technologies are used in surgical interventions in limited anatomical areas where vital structures are located, contribute to improved visualization of the operated area, increasing the accuracy of the surgeon's actions and reducing the likelihood of complications.